THE ASTEROIDS' ROTATION PARAMETERS DETERMINATION USING PHOTOMETRICAL DATA - Burlak, N. R.; Golubovskaya, T. A.; Koshkin, N. L.; Strahova, S. L. (Одеські астрономічні публікації, 2017)
Presented a new method of determination of the asteroid rotation parameters.